Plasmid Mediated mcr-1.1 Colistin-Resistance in Clinical Extraintestinal Escherichia coli Strains Isolated in Poland - Majewski, Piotr; Gutowska, Anna; Smith, David G. E.; Hauschild, Tomasz; Majewska, Paulina; Hryszko, Tomasz; Gizycka, Dominika; Kedra, Boguslaw; Kochanowicz, Jan; Glowiński, Jerzy; Drewnowska, Justyna; Swiecicka, Izabela; et al. (Frontiers in Microbiology, 2021)
Objectives: The growing incidence of multidrug-resistant (MDR) bacteria is an inexorable and fatal challenge in modern medicine. Colistin is a cationic polypeptide considered a “last-resort” antimicrobial for treating of infections caused by MDR Gram-negative pathogens. Plasmid-borne mcr colistin resistance emerged recently, and could potentially lead to essentially untreatable infections, particularly in the hospital and veterinary (livestock farming) setting. In this study, we sought to establish the molecular basis of colistin-resistance in six extraintestinal Escherichia coli strains. Methods: Full structures of six extraintestinal colistin-resistant E. coli bacterial chromosomes and plasmids were recovered with use of both short- and long-read sequencing technologies and Unicycler hybrid assembly. Results: Here we report on the emergence of six mcr-1.1-producing extraintestinal E. coli strains with a number of virulence factors. Mobile pEtN transferase-encoding gene, mcr-1.1, has been proved to be encoded within a type IV secretion system (T4SS)-containing 33.3 kbp IncX4 plasmid pMUB-MCR, next to the PAP2-like membrane-associated lipid phosphatase gene. Conclusions: IncX4 mcr-containing plasmids are reported as increasingly disseminated among E. coli isolates, making it an “epidemic” plasmid, responsible for (i) dissemination of colistin-resistance determinants between different E. coli clones, and (ii) circulation between environmental, industrial, and clinical settings. Great effort needs to be taken to avoid further dissemination of plasmid mediated colistin resistance among clinically relevant Gram-negative pathogens.